Kepercayaan Diri Remaja - Jublina Anthoneta (SANCTUM DOMINE: JURNAL TEOLOGI, 2016)
Adolescence is a critical period of someone’s phsycological developments. In this stage, self actualization is one of important areas are developing. It is formed by various different factors that are combined together to build a teenager’s prespective of their self or their environtment around them. One of crusial elements in self actualization is confidence. It will take significant effect in the next stage of teenager’s development.